BRAKING PRECISION, THE CAR NUMBER IN THE TRAILER AND THE HUMP’’S PERFORMANCE - Zhuravel, V. V. (Science and Transport Progress, 2009)
A form of regression equations is determined, which adequately describe a correlation between the error of braking of cuts and the average speed of their collision on hump tracks, the average length of «window» and the average quantity of setting operations per processed wagon taking into account an influence of quantity of wagons in a cut.